National Security in Yemen and Its Impact on Arab National Security: An Analytical Study of Correlation Factors and Efforts to Develop the Structures of Arab Reconstruction from 1990 to 2010 (The International Journal for Scientific Research, 2025)
This study aimed to explore the relationship between the national security of the Republic of Yemen and Arab national security, focusing on direct influencing factors and the components of national security. It also seeks to highlight Yemen's efforts to develop the structures for reconstructing the unified Arab society. The study employed various scientific study methodologies, including a historical approach that relies on historical phenomena to understand the present circumstances related to comprehensive national security, as well as content analysis approach to examine the study's terminologies derived from books, political documents, and various studies. The study found that the appropriate position of the Great Arab Homeland in international relations can only be achieved under a powerful Arab state capable of protecting international balances and safeguarding its national interests. Furthermore, the national security of each Arab state individually is insufficient to protect the entity of the nation-state. The study also provided a series of recommendations aimed at enhancing Arab unity.
Keywords: National Security; Efforts of the Republic of Yemen; Arab National Security